A case of a calcifying cystic odontogenic tumor with odontoma in a 5-year-old boy. Issue 5 (September 2016) - Moritani, Norifumi; Nakata, Naoki; Yamachika, Eiki; Matsumura, Tatsushi; Nagatsuka, Hitoshi; Iida, Seiji
Abstract: We report a case of calcifying cystic odontogenic tumor (CCOT) with odontoma developing in the deciduous dentition period, and present previously reported cases in Japan. A 5-year-old boy visited a dental clinic because of swelling on his left mandibular buccal alveolar region, and was referred to our department. Clinical examination revealed a 20-mm (in diameter), bone-like, hard mass on the left mandibular buccal gingiva at the first deciduous molar region. A panoramic radiograph showed a 25 mm × 20 mm, unilocular, cystic radiolucent area from the left mandibular second deciduous molar to the first molar region. There were radiopaque tiny flecks at the upper side of the lesion. The clinical diagnosis was a benign tumor of the left mandible. Consequently, tumor enucleation was performed under general anesthesia. Histopathological diagnosis confirmed a CCOT associated with odontoma. Five years after surgery, the left mandibular region has healed well, with no evidence of recurrence.